EARLY REFEEDING AFTER COLORECTAL CANCER SURGERY REDUCES COMPLICATIONS AND LENGTH OF HOSPITAL STAY - Eliani Frizon; José Eduardo de Aguilar-Nascimento; Júlio Cesar Zanini; Mariah Steinbach Roux; Bruna Caroline de Lima Schemberg; Pamela Luiza Tonello; Diana Borges Dock-Nascimento (ABCD: Arquivos Brasileiros de Cirurgia Digestiva)
ABSTRACT BACKGROUND: Multimodal protocols such as Acceleration of Total Postoperative Recovery and Enhanced Recovery After Surgery propose a set of pre- and post-operative care to accelerate the recovery of surgical patients. However, in clinical practice, simple care such as early refeeding and use of drains are often neglected by multidisciplinary teams. AIMS: Investigate whether early postoperative refeeding determines benefits in colorectal oncological surgery; whether the patients’ clinical conditions preoperatively and the use of a nasogastric tube and abdominal drain delay their recovery. METHODS: Retrospective cohort carried out at the Cascavel Uopeccan Cancer Hospital, including adult cancer patients (age ≥18 years), from the Unified Health System (SUS), who underwent colorectal surgeries from January 2018 to December 2021. RESULTS: 275 patients were evaluated. Of these, 199 (75.4%) were refed early. Late refeeding (odds ratio — OR=2.1; p=0.024), the use of nasogastric tube (OR=2.72; p=0.038) and intra-abdominal drain (OR=1.95; p=0.054) increased the chance of infectious complication. Multivariate analysis showed that receiving a late postoperative diet is an independent risk factor for infectious complications. Late refeeding (p=0.006) after the operation and the placement of an intra-abdominal drain (p=0.007) are independent risk factors for remaining hospitalized for more than five days postoperatively. CONCLUSIONS: Refeeding early in the postoperative period reduces the risk of infectious complications. Using abdominal drains and refeeding late (>48h) for cancer patients undergoing colorectal surgery are risk factors for hospital stays longer than five days.